Analisis Faktor-Faktor Yang Mempengaruhi Pengangguran Terdidik Di Indonesia - Marcell E R Sinaga; Noni Rozaini (Jurnal Samudra Ekonomika, 2023)
This research is intended to see the effect of economic growth, provincial minimum wage, and human development index in Indonesia. The data used in this study are secondary data with the type of time series data for the period 2019-2022 and cross section of 34 provinces in Indonesia. This research is quantitative research using linear regression analysis method with fixed Effect Model approach. From this research, it is found that Economic Growth and Human Development Index have a negative and significant effect on Educated Unemployment in Indonesia. Meanwhile, the Provincial Minimum Wage has a negative and significant effect on Educated Unemployment in Indonesia. Simultaneously, Economic Growth, Provincial Minimum Wage, and Human Development Index have a contribution of 99.06% to Educated Unemployment in Indonesia while the remaining 0.94% is explained by other factors that are not in this study.